THE EFFECT OF BUSINESS ETHICS, ENTREPRENEURSHIP BEHAVIOR, AND ORGANIZATIONAL CLIMATE ON LEGAL MICRO, SMALL AND MEDIUM ENTERPRISES PERFORMANCE THROUGH PROFESSIONAL COMMITMENTS IN PASURUAN CITY (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This study aims to analyze the influence of business ethics, entrepreneurial behavior, organizational climate towards professional commitment of MSMEs; analyze the influence of business ethics, entrepreneurial behavior, organizational climate on the performance of MSMEs entrepreneurs; analyze the influence of professional commitment to the performance of MSMEs entrepreneurs, and analyze the influence of business ethics, entrepreneurial behavior, organizational climate on the performance of MSMEs entrepreneurs through professional commitment in Pasuruan East Java. The target population is MSMEs in Pasuruan City which has SIUP of 237 entrepreneurs. In this research the determination of sample size by using Slovin formula, The number of samples in this study as many as 149 entrepreneurs. The sampling technique used is simple proportional random sampling. The analysis technique used is descriptive analysis and Structural Equation Modeling (SEM) Analysis. Business ethics, entrepreneurial behavior, and organizational climate have an effect on professional commitment. Business ethics, entrepreneurial behavior, and organizational climate affect performance. Professional commitment affects performance. Professional commitment is the strengthening (mediation) of business ethics, entrepreneurial behavior and organizational climate on performance..